Suspect zero - Merhige, E. Elias; Eckhart, Aaron; Kingsley, Ben.; Moss, Carrie-Anne, 1970-; Lennix, Harry J.; DeHuff, Nicole; Chapman, Michael, 1935-; Mansell, Clint; Paramount Home Entertainment (Firm) (Hollywood, Calif. : Paramount Home Entertainment, 2005)
An FBI agent pursues a man who himself is chasing Suspect Zero, the ultimate serial killer so mysterious, they're unsure whether he actually exists.
Originally released as a motion picture in 2004.
Special features: Commentary by director; 4 part featurette: "What we see when we close our eyes"; remote viewing demonstration; alternate ending; trailer.
Director of photography, Michael Chapman ; editors, John Gilroy, Robert K. Lambert ; music, Clint Mansell ; costume designer, Mary Claire Hannan ; production designer, Ida Random.
Aaron Eckhart, Ben Kingsley, Carrie-Anne Moss, Harry Lennix, Nicole DeHuff, Kevin Chamberlin, William Mapother, Keith Campbell, Frank Collison.
MPAA rating: R; for violent content, language and some nudity.
DVD, region 1, anamorphic widescreen (1.85:1) presentation; Dolby Digital 5.1.
Keywords: Serial murders -- Drama; Serial murderers -- Drama; Feature films; Video recordings for the hearing impaired